Company Characteristics and Related to Tax Avoidance on Sharia Commercial Banks in Indonesia - Fitriana Hamsyi, Nur; Febriana Dosinta, Nina (International Journal of Scientific Research and Management (IJSRM), 2021)
The sustainability of a country cannot be separated from taxes as the most dominant source of income. However, the realization of tax revenue has not shown the maximum level in meeting the set targets. One of the contributing factors is the low awareness of paying taxes. This study investigates the company characteristics of financial leverage, executive character, profitability, and its relationship with tax avoidance. Sharia commercial banks with observations of 66 banks in six years became the sample in this study. Data processing is done by software E-views. Several findings obtained from the test results prove that financial leverage (DER) positively affects tax avoidance. Meanwhile, the executive character and return on equity do not affect tax avoidance.